The Philosophy of the Life Cycle in Tembang Macapat as an Inspiration for Painting - Wibowo, Reza Mukti; Athian, Muhammad Rahman (Universitas Negeri Semarang, 2025)
This research is a visualization of the human life cycle in each mentrum of tembang macapat, with romanticism as its main concept. The paintings are created using the glaze/glazing technique with a tenebrism lighting approach. The purpose of this study is to visualize the philosophy of the human life cycle in tembang macapat through painting, making it a means of appreciation, education, and local cultural preservation. Additionally, this research aims to present a more communicative artistic approach for younger generations, encouraging them to better understand and appreciate their cultural heritage. The novelty of this study lies in its cultural acculturation approach in visual arts, combining the philosophy of tembang macapat a Javanese cultural heritage with Western romanticism style in painting. Furthermore, it introduces the tenebrism lighting technique to enhance dramatic and emotional depth, a technique rarely used in previous visual representations of tembang macapat. This research has resulted in eleven paintings, each depicting the human life cycle based on the mentrum of tembang macapat. Each artwork is visualized in a romantic style, employing the glaze/glazing technique and tenebrism lighting, emphasizing dramatic elements and visual depth. The findings show that the philosophical values of tembang macapat can be interpreted visually to provide a broader understanding to the public and serve as a learning medium through art. The choice of a romantic style with human figure representations as a visualization of the human life cycle serves to present clear and accessible information. This approach ensures that the artworks are easily understood by a wider audience while inviting viewers to see, feel, and comprehend the meaning behind each phase of life.